Optimalisasi Penggunaan Akad Salam dalam Pembiayaan Sektor Pertanian Syariah untuk Meningkatkan Produktivitas Petani - Hendro Lisa; Risviyaldi Risviyaldi (Jurnal Bisnis, Ekonomi Syariah, dan Pajak, 2025)
The agricultural sector plays a crucial role in the Indonesian economy, contributing significantly to Gross Domestic Product (GDP), employment, and national food security. Conventional financing is often poorly suited to the unique characteristics of the agricultural sector, prompting the exploration of more adaptive alternatives. Islamic banking, with its principles of fairness and risk-sharing, offers innovative financing solutions. One such contract with significant potential but underutilized is the Salam contract, a purchase-and-sell contract where payment is made upfront and goods are delivered at a later date. This study aims to analyze the characteristics of the Salam contract in depth, identify challenges and opportunities in its implementation in the Islamic agricultural sector, and formulate strategies for optimizing its application. Using a qualitative descriptive research method based on literature review and comparative analysis, this article finds that the Salam contract offers an effective financing solution for farmers' working capital needs, price risk mitigation for farmers, and supply security for buyers. Key challenges include the risk of crop failure, quality risk, moral hazard risk, and limited supporting infrastructure and market understanding. Optimizing the Salam contract can be achieved through the development of innovative contract models, strengthening risk management through takaful instrumentation, utilizing digital technology, improving Islamic financial literacy, and collaboration between stakeholders. The implications of this research are expected to provide practical guidance for Islamic financial institutions, farmers, and policymakers to create a more inclusive and sustainable Islamic agricultural financing ecosystem. With the right approach, the Salam contract has the potential to become a key instrument in Islamic agricultural financing. Its widespread implementation can drive the transformation of the agricultural sector toward a more productive and equitable direction. Sustainable efforts are needed to ensure its effective implementation in the field.